ANALYSIS OF BBM, LEC, AND SERK EXPRESSIONS IN CALLUS OF SUGARCANE (Saccharum officinarum L.) AT SOMATIC EMBRYOGENESIS DEVELOPMENT STAGES - Lisa Prastuti Anggraeni; Firdha Narulita Alfian; Laily Ilman Widuri; Parawita Dewanti (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Callus formed in somatic embryogenesis is divided into two types, embryogenic and non-embryogenic callus. Embryogenic callus can be distinguished by the expression of genes as markers related to somatic embryogenesis which are expected to be used as markers to detect callus that has embryogenic capabilities in sugarcane. The aim of this study was to determine the expressions of somatic embryogenesis-related genes in sugarcane. The genes analysis was carried out using somatic embryogenesis callus and using a kit for RNA analysis. Results showed that there were expressions of Baby Boom (BBM), Leafy Cotyledon (LEC), dan Somatic Embryogenesis Receptor Like-Kinase (SERK) gene with specific primer of those three genes, which were collected from embryogenic callus in mass, globular, scutelar, and coleoptilar pre-embryo stages, meanwhile there were no expressions of those genes collected from non-embryogenic callus. Amplification result from PCR product of cDNA using three gene primers detected were in 500 bp for BBM, 400 bp for LEC, and 700 bp for SERK gene. Kalus yang terbentuk pada embriogenesis somatik terbagi menjadi 2 jenis, yatu kalus embriogenik dan non embriogenik. Kalus embriogenik dapat dibedakan dengan adanya ekspresi gen sebagai penanda karena adanya proses somatik embriogenesis yang nantinya diharapkan dapat digunakan sebagai marka untuk mendeteksi kalus yang memiliki kemampuan embriogenik pada tanaman tebu. Tujuan dari penelitian ini yaitu untuk mengetahui ekspresi gen yang diduga terkait proses embriogenesis somatik pada tanaman tebu. Analisis gen terkait proses embriogenesis tersebut dilakukan dengan menggunakan kalus hasil embriogenesis somatik, dan penggunaan kit untuk analisis RNA. Hasil penelitian menujukkan bahwa terdapat ekspresi gen Baby Boom (BBM), Leafy Cotyledon (LEC), dan Somatic Embryogenesis Receptor Like-Kinase (SERK) dengan primer spesifik ketiga gen tersebut, yang diambil dari sampel kalus embriogenik fase pre-embryo mass, globular, skutelar, dan koleoptilar, namun tidak adanya ekspresi ketiga gen tersebut pada kalus non embriogenik. Hasil amplifikasi sampel produk PCR dari cDNA menggunakan ketiga primer gen yang terdeteksi memiliki ukuran sebesar 500 bp untuk gen BBM, 400 bp untuk gen LEC, dan 700 bp untuk gen SERK.